Word Search on Word Wall to Improve Students’ Vocabulary at SMPT Al-Madani, Cikarang Utara, Bekasi - Azis, Astuti; Mala’a Lana Zulfa (Universitas Terbuka, 2025)
In this research, word search media was used on the word wall to determine the increase in vocabulary of AL-MADANI SMPT students. English is a language that is used as an international language, so many people learn this language, especially to increase their vocabulary in communicating with each other. This is a class action research which was divided into 2 cycles, where each cycle consisted of planning, implementation, observation, and reflection. Word search is one of the templates on the word wall to facilitate a more interactive and engaged class. The researchers found that in the first cycle, students’ engagement increased by 65%, while in the second cycle, students' engagement reached 95%. This engagement contributes to students’ achievement progress. This research also helps teachers create creative and innovative media.